Diketopyrrolopyrrole J‐Aggregates Formed by Self‐Organization with DNA. Issue 6 (22nd April 2014) - Tsuto, Koji; Nakamura, Mitsunobu; Takada, Tadao; Yamana, Kazushige
Abstract Bis(2‐thienyl)diketopyrrolopyrrole with two ZnII‐cyclens (ZnCyc‐DPP) was designed and synthesized to evaluate the selective binding of ZnII‐cyclen with thymine base in single‐strand DNA as a tool for the construction of a highly ordered multichromophore system on DNAs. Through UV/Vis titrations, gel filtration chromatography, and circular dichroism spectroscopy, ZnCyc‐DPP formed J‐type DPP aggregates with oligo‐dTn DNAs. The DPP aggregates absorbed on a gold electrode exhibited good photocurrent responses. The present results show that binding ZnII‐cyclen–chromophore conjugates and thymine bases together is a powerful tool for preparing DNA‐templated multichromophoric systems with specific functions.